The overlap of cooperative learning and directed discovery and its impact on the development of some basketball skills for female students (Journal of the College of Basic Education, 2022)
The importance of the physical education lesson for the student's growth, personality, social relations, and his ability to create and innovate. It also included the need to use new methods of learning that help the student to increase his self-confidence and benefit from the available information in finding new relationships. As for (the importance of research), it appears through the use of the overlap between cooperative learning and guided discovery in developing some basketball skills for female students.